Spatial Analysis of the Circular Migrant Workers Places of Origin in Bekasi Regency - Sari, Ariyani Puspita; Arsanti, Vidyana; Meliyani, Siti (Universitas Pendidikan Ganesha, 2024)
Bekasi Regency in West Java Province attracts many migrants from other regions due to the presence of numerous large industrial companies that support the local economy and income. One such company is PT. Suzuki Indomobil Motor Tambun, located in South Tambun District, which operates in the automotive industry. This study aims to identify the factors influencing circular migration and the distribution of the regions of origin of workers engaging in this migration. The methods employed include qualitative descriptive analysis, while spatial analysis is used to assess the distribution of the workers' regions of origin. Primary data were collected to identify migrant characteristics, including age, gender, region of origin, place of residence, and mode of transportation. The results indicate that the motivation to work at PT. Suzuki Indomobil Motor Tambun stems from greater job opportunities compared to the migrants' places of origin, as well as higher wages. The primary reason migrants do not seek employment in their home regions is due to a lack of job opportunities. Furthermore, the origins of circular migrant workers are spread across 12 provinces, with the majority coming from Central Java.